Upaya Meningkatkan Motivasi Belajar Siswa Melalui Permainan dalam Pembelajaran PJOK di Kelas VIII SMP N 28 Surabaya - Fauza Akbar Shomat; Bambang Ferianto Thahyo Kuntjoro (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2024)
This investigate centers on the moo learning inspiration of understudies in lesson VIII SMP Negeri 28 Surabaya. The reason of this investigate is to get information or data and talk about approximately expanding students' learning inspiration by utilizing the play learning demonstrate. This sort of investigate is classroom activity investigate with arranging, usage, perception and reflection methods. This classroom activity investigate was conducted in lesson VIII SMP Negeri 28 Surabaya with a add up to of 30 understudies. This investigate was conducted for two cycles and information collection was carried out utilizing perception sheets, interviews and documentation which were analyzed by rate and subjectively. The comes about of this consider found an increment in understudy learning results gotten from perception sheets carried out after cycles I and II by playing learning recordings